MORC2 controls HIF-1α stability via an HDAC4-dependent mechanism to regulate erythropoiesis - Yanfei Tang; Boqi Zhang; Tingting Xue; Yunzhang Liu; Yun Li; Yuchao Gu; Jiejie Hao; Ling Lu (Proceedings of the National Academy of Sciences, 2026)
The hypoxia-inducible factor (HIF) signaling pathway is essential for cellular adaptation to low oxygen. Although the canonical PHD-pVHL pathway that mediates HIF-α degradation under normoxia is well established, alternative regulatory mechanisms remain poorly understood. Here, we identify Microrchidia family CW-type zinc-finger 2 (MORC2) as a negative regulator of HIF-α. In zebrafish, CRISPR/Cas9-generated morc2 mutants developed polycythemia, systemic hypoxia, and constitutive activation of the HIF pathway. Mechanistically, MORC2 counteracts histone deacetylase 4 (HDAC4) by competing for HIF-1α binding. Loss of MORC2 enhances HDAC4 recruitment to HIF-1α, reducing acetylation at lysine 629 and preventing proteasomal degradation of HIF-1α. These results define a regulatory mechanism in which MORC2 modulates HIF-1α stability via HDAC4 mediated deacetylation, shedding light on hematopoiesis and HIF-related disorders.